Pola Komunikasi Gigolo dalam Prostitusi Daring di X (Universitas 17 Agustus 1945 Surabaya, 2023)
The presence of social media in society provides convenience in various aspects, one of which is to facilitate the transaction process in marketing for the promotion of goods and services, whether legal or illegal such as prostitution which is also carried out by men or gigolos. One of the social media used in online prostitution is the Twitter application which has changed its name to X. This study aims to determine the communication patterns in online prostitution carried out by gigolos in X. This research is a qualitative research using phenomenological method. This research was conducted in Makassar city. Primary data is in the form of interviews with informants and secondary data is in the form of books, dissertations, thesis journals, and the internet. The data collected are the results of interviews with informants consisting of three people. The conclusion of the research shows that online prostitution carried out by gigolos in X uses circular communication patterns using the DeFluer model which adds mass media and feedback to the model. Related to the increasing number of online prostitution cases on social media, especially X, it is hoped that the role of the government, in this case, the Ministry of Communication and Information Technology, will be more assertive in blocking accounts related to online prostitution. Keywords: Communication Pattern, Online Prostitution, Gigolo, X